Bathymetry and Its Applications - Blondel, Philippe (IntechOpen, 2012)
Bathymetry is the only way to explore, measure and manage the large portion of the Earth covered with water. This book ,presents some of the latest developments in bathymetry, using acoustic, electromagnetic and radar sensors, and in its applications, from gas seeps, pockmarks and cold-water coral reefs on the seabed to large water reservoirs and palynology. The book consists of contributions from internationally-known scientists from India, Australia, Malaysia, Norway, Mexico, USA, Germany, and Brazil, and shows applications around the world and in a wide variety of settings.